PELAKSANAAN KONSEP KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DALAM MENINGKATKAN MUTU MADRASAH DI MAN 1 GARUT - Eep Saepuloh; Ummu Salamah; Nenden Munawaroh (STKIP Pesisir Selatan, 2026)
This research analyzes the transformation of MAN 1 Garut into a leading madrasah through transformational leadership amidst intense educational competition. It aims to analyze the construction of concepts, implementation, and determinants, while reconstructing an effective leadership model to enhance institutional quality. Utilizing a descriptive qualitative method, data were collected through in-depth interviews with nine key informants, observation, and documentation, validated via triangulation.The results indicate that leadership is operationalized through a